Common types of visualization of chemical structure - Hanson, Robert M. (Henry Stewart Talks, 2011)
Representing chemical compounds, Typical 3D molecular visualizations, Molecular Surfaces, Van der Waals, Solvent excluded, Solvent accessible, Mapping data onto molecular surfaces, Construction of surfaces, Isosurfaces, Marching Cubes algorithm